2013
DOI: 10.1177/1046496413498119
|View full text |Cite
|
Sign up to set email alerts
|

Justice Climate and Peer Justice Climate

Abstract: We provide an empirical examination of peer justice climate, defined as team-level judgments of the fairness with which coworkers generally treat one another, and justice climate, defined as team-level judgments of the fairness with which the team is collectively treated by an authority figure. Based on previous theoretical work, we tested a hierarchical structural model determining that peer justice climate was best represented as three first-order factors, which combine into a single second-order dimension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
92
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(100 citation statements)
references
References 80 publications
(163 reference statements)
5
92
1
2
Order By: Relevance
“…In these teams, peer justice promoted effective team processes, which, in turn, engendered citizenship behaviours and a better final grade. In a later study with a similar sample, Li et al (2013) were unable to replicate the findings on performance. However, these authors found that peer justice predicted team satisfaction through the mediating role of cooperative teamwork processes.…”
Section: Peer Justicementioning
confidence: 65%
See 4 more Smart Citations
“…In these teams, peer justice promoted effective team processes, which, in turn, engendered citizenship behaviours and a better final grade. In a later study with a similar sample, Li et al (2013) were unable to replicate the findings on performance. However, these authors found that peer justice predicted team satisfaction through the mediating role of cooperative teamwork processes.…”
Section: Peer Justicementioning
confidence: 65%
“…Justice climate is well consolidated in the literature, helping to predict worker attitudes (Spell & Arnold, 2007), job performance (Naumann & Bennett, 2000), and absenteeism (Colquitt et al, 2002). Li et al (2013) recently conducted an empirical examination of the factorial structure of justice climate. Consistent with the tendency towards an overall approach to justice (e.g., Ambrose & Arnaud, 2005, Li et al (2013) observed that justice climate was best represented through a hierarchical structure that combined the first-order facets of this construct (distributive, procedural, interpersonal, and informational) into a superordinate construct-justice climate as a second-order factor.…”
Section: Justice Climatementioning
confidence: 99%
See 3 more Smart Citations